Inventory of sustainable land management (SLM) practices for Uzbekistan’s marginal landscapes - Haddad, Mira; Lopez Montoya, Itzel; Akramkhanov, Akmal (2023)
A systematic literature review was performed to compile sustainable land management (SLM) practices with a focus on water storage and harvesting for marginal landscapes in Uzbekistan. In total, 18 SLM practices have been listed, described, and their biophysical criteria established.